Agency in transit: social negotiations of Pakistani women in international higher education - Ashfaq, F (2023)
This study is an exploration of the agencies afforded to Pakistani women who receive international postgraduate higher education. It examines (a) the influence of various social relations on their agency and (b) evaluations of surrounding processes and ultimate outcomes of agentive decisions. Qualitative, semi-structured interviews are conducted with ten globally-situated Pakistani women who completed postgraduate and graduate outside of Pakistan up to six years ago. The work of Chandra Talpade Mohanty, Lila Abu-Lughod, and Saba Mahmood is drawn to contextualise the complex nuances of localised agency of Pakistani women which transcends liberal feminist and Western notions. The research - by examining women’s navigations through higher education - uniquely contributes to scholarship surrounding their agency by presenting a process-over-outcome conceptualization that expands traditional/universalised understandings. In doing so, it shows us how little we know about the diversity of women’s agency and the pathways through which they conceptualise their power. This work thus highlights the need for deeper engagement with women’s lived experiences surrounding agentive decision-making processes.